Měkkýši NPR Strabišov – Oulehla u Litenčic (jižní Morava, Česká republika) - Jaroslav Vašátko (Malacologica Bohemoslovaca, 2007)
The paper presents an inventory of molluscan fauna of the Strabišov-Oulehla NNR near the village of Litenčice (South Moravia, Czech Republic). This is the first report concerning Mollusca of this reserve. Altogether 32 mollusc species have been recorded during years 2004-2005. Forest fringe vegetation, Carpathian Oak – Hornbeam forest, broad – leaved dry grassland and riparian vegetation- habitats were investigated. The species Cepaea vindobonensis, Xerolenta obvia, Granaria frumentum, Chondrula tridens, and Euomphalia strigella were recorded in broad-leaved dry grassland habitats, thermophilous oak forests and Carpathian Oak – Hornbeam forests which were inhabited by Monachoides incarnatus, Alinda biplicata, Merdigera obscura, Fruticicola fruticum, Limax cinereoniger, and Arion subfuscus, on the moister places Carychium tridentatum and Columella edentula was also found. The forest fringe vegetation was a habitat of Euomphalia strigella, Cepaea vindobonensis, Xerolenta obvia, and Helix pomatia; in riparian vegetation of the nameless tributary of the Litava River Trichia hispida, Helix pomatia, Monachoides incarnatus, Arion silvaticus, Laciniaria plicata, Cochlicopa lubrica were also recorded.